ANALISIS KEPUASAN KONSUMEN TERHADAP LAYANAN COMMUTER LINE BERDASARKAN MARKETING MIX 7P LINTAS MANGGARAI-CIKARANG - Tansah Bagas Prakosa Jati; Yenita (PAPATUNG: Jurnal Ilmu Administrasi Publik, Pemerintahan dan Politik, 2022)
Transportation is currently an important need besides clothing, food and shelter for every individual who is active, especially in metropolitan areas such as Jakarta, Bogor, Depok, Tangerang and Bekasi (Jabodetabek) which really require high mobility and demands punctuality is a challenge for transportation provider. KRL Commuter Line as a rail-based urban transportation service provider has the ability to answer the mobility needs of urban communities (Jabodetabek). However, this capability must be supported by qualified service quality, one of which is by implementing the 7P (Marketing Mix) marketing mix for KRL Commuter Line services. Lintas Manggarai-Cikarang is one of the KRL Commuter Line corridors that is included in the category of high passenger volume, so service to service users will be seen based on product factors, price, place, people, promotion, process and physical evidence and their relationship to customer satisfaction KRL Commuter Line crossing Manggarai-Cikarang. The results of the SEM-PLS analysis of product, price, promotion, people, and process factors have a significant value on customer satisfaction. However, the physical evidence and place factors do not have a significant effect on customer satisfaction. Furthermore, in future research, it is hoped that factors that do not have significance can be studied in more depth.